Loss of FCoV-23 spike domain 0 enhances fusogenicity and entry kinetics - M. Alejandra Tortorici; Annette Choi; Cecily A. Gibson; Jimin Lee; Jack T. Brown; Cameron Stewart; Anshu Joshi; Sheri Harari; Isabelle Willoughby; Catherine Treichel; Elizabeth M. Leaf; Jesse D. Bloom; et al. (Nature, 2025)
Abstract The ability of coronaviruses to recombine and cross species barriers affects human and animal health globally and is a pandemic threat1,2. FCoV-23 is a recently emerged, highly pathogenic recombinant coronavirus responsible for a widespread outbreak of feline infectious peritonitis. Here we report cryogenic electron microscopy structures of two FCoV-23 spike isoforms that correspond to the in-host loss of domain 0 observed in clinical samples. The loss of domain 0 markedly enhances the fusogenicity and kinetics of entry into cells and possibly enables biotype switching and lethality. We show that FCoV-23 can use several aminopeptidase N orthologues as receptors and reveal the molecular determinants of receptor species tropism, including a glycan that modulates human receptor engagement. We define antigenic relationships among alphacoronaviruses that infect humans and other mammalian species and identify a cross-reactive alphacoronavirus monoclonal antibody that inhibits FCoV-23 entry. Our results pave the way for the development of vaccines and therapeutics that target this highly pathogenic virus.